ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERILAKU KONSUMEN DALAM PEMBELIAN PRODUK MIE INSTAN DI KOTA MALANG - Iriani, Nur Ida (Fakultas Ekonomi, UIN Maliki Malang, 2010)
The objectives of the research are to know the concurrent effects of educational factors of consumers along with the price, quality, distribution, and promotion of towards the consumers' behavior in purchasing instant noodle, and to identify what factors have a dominant effect on the consumers' behavior in purchasing instant noodle in Malang. After an examination of 200 respondents by means of multiple linear regression method, the study found that: (1) F count value is 34.677, meaning that it is larger than F table (2.14). This indicates that there are significant concurrent effects of educational factors of consumers along with the price, quality, distribution, and promotion of instant noodle towards the consumers' behavior in purchasing instant noodle in Malang. Thus, the first hypothesis is accepted. (2) Among the independent variables that were examined, price has a dominant and significant effect on consumers' decision in purchasing instant noodle. Thus, the second hypothesis is accepted. (3) Viewed from the effects of individual factors on consumers' behavior in purchasing instant noodle, then: (a) Price has a significant effect of 12.15% on the purchase of instant noodle. (b) Education and income have a significant effect on the purchase of instant noodle. (c) Quality, distribution, and promotion have a significant but little effect on the purchase of instant noodle.